Macroeconomic and Bank-Specific Determinants of Malaysian Bank Profitability: Evidence During the Period of 2008 Global Financial Crisis - Nurul Hazwani, Ramli (2014)
This dissertation analyzes the determinants of commercial bank profitability in Malaysia for the period 2006-2012. This dissertation also examines whether 2008 global financial crisis affects bank profitability in Malaysia. Since the sample comprises foreign and local banks, this dissertation also tests whether there is significant difference between foreign and local banks in the aspect of profitability, as generally, foreign banks have larger capital than that of local banks. From the fixed effect estimation analysis, the findings suggest that Malaysian banks with a larger capital and higher credit quality exhibit high profitability level. The findings also demonstrate that bank size has a negative relationship with bank profitability, implying that bigger banks have lower profits than that of small banks. The results also do not support that foreign banks are more profitable than that of local banks in the period studied. In the aspect of macroeconomics determinants, the results suggest that GDP is not the main determinant of Malaysian bank profitability , while on the contrary, inflation rate significantly impact bank profitability in Malaysia. Interestingly, this dissertation does not find conclusive evidence to support that the 2008 global financial crisis affects bank profitability in Malaysia.